Optimasi Biaya Transportasi Logistik Dan Penentuan Lokasi Gudang Baru Menggunakan Metode Center Of Gravity (COG) - Dewi, Fitriya Gemala; Aprisi Anansyah, M. Dikya; Hindratmo, Astria; Wahyu Oktavia, Chendrasari (Journal of System Engineering and Technological Innovation, 2024)
To support product delivery, there is a need for distribution centers to send in a timely manner to various regions in Java Island. Research at PT. XYZ has a goal to determine the location of distribution centers that are effective and efficient in terms of minimizing transportation costs, because currently there are only old warehouses that are too far from distributors, with this distribution center, we can find out the cost comparison of product delivery to the intended distributor, and can also find out whether the center of gravity method can be applied to PT. XYZ or not. The case study of this research is product delivery in the East Java region by collecting product delivery data at PT. XYZ. This study uses Google Maps software to determine the coordinates of each customer, then calculates and processes the data using the Center of Gravity method. The research results obtained are the location of the new distribution center which is located in Kebontemu Hamlet, Peterongan District, Jombang Regency. With the new distribution center optimized by grouping, the effect on reducing transportation costs is 47%, and distances are 54%.